Looking at plant cell cycle from the chromatin window - Desvoyes, Bénédicte; Fernández-Marcos, María; Sequeira-Mendes, Joana; Otero, Sofía; Vergara, Zaida; Gutierrez, Crisanto (Frontiers in Plant Science, 2014)
The cell cycle is defined by a series of complex events, finely coordinated through hormonal, developmental and environmental signals, which occur in a unidirectional manner and end up in producing two daughter cells. Accumulating evidence reveals that chromatin is not a static entity throughout the cell cycle. In fact, there are many changes that include nucleosome remodeling, histone modifications, deposition and exchange, among others. Interestingly, it is possible to correlate the occurrence of several of these chromatin-related events with specific processes necessary for cell cycle progression, e.g. licensing of DNA replication origins, the E2F-dependent transcriptional wave in G1, the activation of replication origins in S-phase, the G2-specific transcription of genes required for mitosis or the chromatin packaging occurring in mitosis. Therefore, an emerging view is that chromatin dynamics must be considered as an intrinsic part of cell cycle regulation. In this article, we review the main features of several key chromatin events that occur at defined times throughout the cell cycle and discuss whether they are actually controlling the transit through specific cell cycle stages.